PENERAPAN SEMA NOMOR 3 TAHUN 2015 DALAM PEMBUATAN PUTUSAN PIDANA BAGI PELAKU PENYALAHGUNA NARKOTIKA - Samuel Samosir (Fakultas Ilmu Sosial dan Humaniora, 2022)
The enactment of SEMA Number 3 of 2015 is as a reference for judges in giving decisions for perpetrators of Narcotics crime who turned out to be proven in the trial only as Narcotics abusers as stipulated in Article 127 of the Narcotics Law, so that even though the defendant was charged with the provisions of Article 111 or 112 of the Narcotics Law which has provisions a special minimum sentence, but judges can give imprisonment under the special minimum provisions, but what needs to be noted is that the SEMA regulation Number 3 of 2015 in addition to being able to provide imprisonment under the special minimum criminal provisions, SEMA Number 3 of 2015 actually also implies that there are the judge's obligation to pay attention to whether the defendant is just a drug abuser or addict, this is a concern because the criminal provisions imposed will be different if the defendant is proven to be a narcotics addict who should not be sentenced to prison, but needs to be done r rehabilitation. The focus of the study in this article is to explore how judges apply SEMA Number 3 of 2015 in making decisions so that they remain in accordance with the purpose of the formation of the Narcotics Law itself, which is in addition to prevention but also prevention and healing efforts for narcotics abusers.